KOMUNIKASI INTERPERSONAL DI KALANGAN KARYAWAN BADAN PERPUSTAKAAN DAN KEARSIPAN DAERAH (BAPUSIPDA) JAWA BARAT DAN HUBUNGANNYA DENGAN KINERJA TENAGA PERPUSTAKAAN - Prasetyo W., Anton; Winoto, Yunus (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2016)
INTERPERSONAL COMMUNICATION AMONG EMPLOYEES OF REGIONAL OFFICE OF LIBRARY AND ARCHIVES (BAPUSIPDA) WEST JAVA AND ITS CONNECTION WITH THE PERFORMANCE OF LIBRARIANÂ This study aims to determine the relationship between interpersonal communications in the West Java Environmental BAPUSIPDA employees with the performance of library personnel. This research was conducted in the Library and Archives of West Java Province. The approach used in this study using a quantitative approach to research the type of correlation. The population in this study is employees BAPUSIPDA at the library with a random sampling technique (simple random sampling). For data collecting technique is done through questionnaires, interviews, observation and literature study. Based on the results of the study can be argued that that there hubunan between interpersonal communication on energy performance libraries in the Library Board and the Regional Archives (BAPUSIPDA), West Java. While specifically be presented the following results 1). There hubunan between aspects of transparency (openness) in kalngan employees primarily to the performance of library personnel, 2). There is a relationship between aspects of empathy (empathy) among employees with performance library personnel, 3). There is a relationship between being supportive (supportiveness) between each of brackish employees with the performance of library personnel, 4). There is a relationship between positive attitudes (positiveness) among the employees with the performance of library personnel, 5). There is a relationship between the understandings of equality (equality) among the employees with the performance of library personnel.Kata kunci: interpersonal communication, performance, public libraryÂ ABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan antara komunikasi antarpersonal di lingkungan karyawan Badan Perpustakaan dan Kearsipan Daerah (BAPUSIPDA) Jawa Barat dengan kinerja tenaga perpustakaan. Penelitian ini dilakukan di Badan Perpustakaan dan Kearsipan Daerah, Provinsi Jawa Barat. Pendekatan penelitian yang digunakan menggunakan pendekatan kuantitatif dengan jenis penelitian korelasi. Populasi dalam penelitian ini adalah karyawan BAPUSIPDA di bagian perpustakaan dengan teknik pengambilan sampel secara random (simple random sampling). Teknik pengumpulan data dilakukan melalui angket, wawancara, observasi, dan studi kepustakaan. Hasil penelitian menunjukkan bahwa terdapat hubungan antara komunikasi interpersonal terhadap kinerja tenaga perpustakaan di lingkungan BAPUSIPDA Jawa Barat yang dapat dirinci sebagai berikut. Pertama, terdapat hubungan antara aspek keterbukaan (openness) di kalangan karyawan dengan kinerja tenaga perpustakaan. Kedua, terdapat hubungan antara aspek empati (empathy) di antara karyawan dengan kinerja tenaga perpustakaan. Ketiga, terdapat hubungan antara sikap mendukung (supportiveness) di antara masing-masing karyawan dengan kinerja tenaga perpustakaan. Keempat, terdapat hubungan antara sikap positif (positiveness) di kalangan karyawan dengan kinerja tenaga perpustakaan. Kelima, terdapat hubungan antara pemahaman kesetaraan (equality)Â di antara karyawan dengan kinerja tenaga perpustakaan.Kata kunci: komunikasi antarpribadi, kinerja, perpustakaan umum.